In-situ stress evolution and its correlation with structural characteristics of GaN buffer grown on Si substrate using AlGaN/AlN/GaN stress mitigation layers for high electron mobility transistor applications - Lingaparthi, R. (2021)
In-situ stress evolution as a function of thickness has been investigated and correlated with the structural properties and surface morphology of GaN buffer layer grown on AlGaN/AlN/GaN stress mitigating layers (SMLs). For comparison, GaN buffer was also grown on AlN/GaN SMLs. AlGaN/AlN/GaN SMLs exhibited efficient stress mitigation characteristics resulting in higher compressive mean stress during the growth and convex bow at the end of the growth. Horizontal screw-type misfit dislocations generated at the GaN/AlGaN and AlGaN/AlN interfaces were attributed to the stress mitigation property. The residual compressive stress in the GaN buffer was found to be lower with the AlGaN/AlN/GaN SMLs, which resulted in rough surface morphology. Increased V/III ratio used for GaN buffer growth was found to result in reduced stress relaxation at the interface leading to higher residual compressive stress and enhanced diffusion of ad-atoms. This consequently reduced the kinetic roughening and improved surface morphology. Thus, stress engineering by using AlGaN/AlN/GaN SMLs and by changing of the V/III ratio of GaN buffer, the mean stress of heterostructure was controlled and relatively smoother surface morphology was achieved, respectively. Reasonably good uniformity in electrical characteristics with a standard deviation of 7%, 1% and 8% for the sheet resistance, carrier concentration and mobility, respectively, were achieved for GaN high-electron-mobility transistor heterostructures across the 100 mm substrate.